The Effect of Using the Listening Triangle Strategy in Providing the Seventh-Grade Students with Some Listening Comprehension Skills in the Arabic Language Subject for Non-Native Speakers - Lajan Perbal Mahmood (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The current research aimed at identifying the effect of using the listening triangle strategy in providing the seventh-grade students with some listening comprehension skills in the arabic language subject for non-native speakers. The researcher used the experimental curriculum and selected a sample of 84 students who were randomly distributed to two experimental and controlling (testing –controlled) groups, where the group studied the experimentation according to the strategy of the listening triangle and the control group in the usual way, and the researcher prepared an objective test of 72 paragraphs to measure the skill of listening understanding. The results of the study showed a statistically significant difference between the average experimental group grades and the controlling group scores in the application of the remote test of the skill of understanding in the seventh-grade students.